AUDIT DELAY DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN PUBLIK: LITERATUR REVIEW PERIODE 2020-2024 - Muh. Khairil Amri; Keisya Putri Salsabila; Andi Ratu Zaqhila; Fildzah Nur Aini R; Fina Ruzika Zaimar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to review and synthesize recent research on audit delay and its influencing factors in public companies in Indonesia during the 2020–2024 period. Audit delay refers to the time lag between the end of a company’s fiscal year and the publication of its audited financial statements, which affects the timeliness and relevance of financial information. Using a Systematic Literature Review (SLR) approach, this study analyzed 15 selected articles obtained from Google Scholar and other academic databases. The review identified key determinants that consistently influence audit delay, including profitability, firm size, auditor opinion, solvency, reputation of the Public Accounting Firm (KAP), auditor switching, and corporate governance mechanisms. Profitability and auditor opinion were found to be the most dominant variables, where highly profitable firms tend to complete audits faster, while companies receiving non-unqualified opinions experience longer delays. The findings also indicate that external factors such as the COVID-19 pandemic contributed to extended audit completion times due to limited access and operational disruptions. This literature review emphasizes that audit delay is a multidimensional phenomenon influenced by both internal and external factors, highlighting the importance of improving corporate governance, internal control, and financial reporting systems to ensure timely and transparent audits.